Columnar to equiaxed transition in Al-Mg(-Sc)-Zr alloys produced by selective laser melting. (1st March 2018) - Yang, Kun V.; Shi, Yunjia; Palm, Frank; Wu, Xinhua; Rometsch, Paul
Abstract: The addition of 1.08 wt% Sc to an Al-Mg-Zr alloy produced by selective laser melting modifies the highly coarse columnar grain structure to significantly refined columnar grains separated by sub-micron equiaxed grains at the melt pool boundaries. The latter nucleate mainly from the Al3 Sc particles in the remelting zone. An almost fully equiaxed grain structure was achieved by increasing the applied volumetric energy density from 77.1 J/mm 3 to 154.2 J/mm 3 and the platform temperature from 35 °C to 200 °C, due to the combined effects of potent nuclei, increased remelting zone volumes and reduced thermal gradients. Graphical abstract: